Ecomimesis: A Sustainable Design Paradigm Ecomimetic Solutions to Ecosystem Homeostatic Imbalances - C. Woo, Lillian (European Journal of Sustainable Development, 2017)
In the last fifty years empirical evidence has shown that climate change and environmental degradation are largely the results of increased world population, economic development, and changes in cultural and social norms. During this time period, there have been over 500 international agreements to stem the deterioration of the land, sea, and air. Despite all the evidence and treaties, however, climate change is getting worse with ever increasing air and water pollution, soil and ocean degradation, and ecosystem decline. Based on extensive research, this paper provides an analysis of the negative anthropogenic impact on the ecosystem and proposes a new design solution to mitigate and repair environmental degradation: ecomimesis. It is different from other design models because it incorporates all the major components of the ecosystem and designs built and un-built ecosystems to minimize adverse effects and help stabilize the environment. Using nature as its template, econmimesis conserves, repairs, and improves existing ecosystems. This article uses homeostasis as an example of possible ecomimetic designs. It is described with emphasis on the damage inflicted by anthropogenic actions. It primary focus is to propose ecomimetic solutions to repair and mitigate the damage in both the built and unbuilt ecosystems. While there is no single solution to the environmental challenge, ecomimesis represents a comprehensive design paradigm that will slow and correct environmental decline. Ecomimesis represents an innovative and broad change in the way we design and use our ecosystems in order to support an ever growing world population. Keywords: Climate change, Ecomimesis, Ecosystems, Green Infrastructure, Homeostasis, Sustainable design